Six-item cognitive impairment test (6-CIT)’s accuracy as a cognitive screening tool: best cut-off levels in emergency department setting - Salis, Francesco; Pili, Daniela; Collu, Manuel; Serchisu, Luca; Laconi, Rosanna; Mandas, Antonella (Frontiers in Medicine, 2023)
Nowadays, elderly patients represent a significant number of accesses to the Emergency Department (ED). Working rhythms do not allow to perform complete cognitive analysis, which would, however, be useful for the health care. This study aims to define the optimal cut-off values of the six-item Cognitive Impairment Test (6-CIT) as a cognitive screening tool in ED. -METHODS This study included 215 subjects, evaluated at the Emergency Department of the University Hospital of Monserrato, Cagliari, Italy, from July to December 2021. The accuracy of 6-CIT as a cognitive screening tool was assessed by comparison with Mini Mental State Examination (MMSE).The correlation coefficient between the two tests was -0.836